1995
DOI: 10.3109/10799899509045220
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling of Human D2, D3, and D4 Dopamine Receptors in HEK293 Cells

Abstract: The D2 dopamine receptor is known to be functionally coupled to the inhibition of adenylate cyclase when expressed in a number of mammalian cell lines. However, functional coupling of the recently discovered D3 and D4 dopamine receptor subtypes has been more difficult to demonstrate. In this study, human D2, D3 and D4 receptors were stably expressed separately in human embryonic kidney cells (HEK 293). In these cells, activation of D2, D3 or D4 receptors resulted in the inhibition of forskolin-stimulated adeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
2
39
0
1
Order By: Relevance
“…Although D3 receptors are more restricted in their distribution compared to their D2 counterparts, several studies have shown that these receptors can couple to G-proteins that link to similar effector mechanisms that include the regulation of calcium currents and inhibition of adenylate cyclase (Seabrook et al, 1994a;Chio et al, 1994;McAllister et al, 1995 (DeMattos et al, 1993). Furthermore, in functional assays this ligand is an agonist at cloned human D3 receptors (McAllister et al, 1995) and also modulates midbrain dopamine cell function (DeWald et al, 1990). Estimates of the binding selectivity of agonists for D3 over D2 receptors are influenced by whether one compares the high or low affinity states of the receptors (e.g.…”
Section: Functional Effects Of (+)-Pd 128907mentioning
confidence: 99%
See 1 more Smart Citation
“…Although D3 receptors are more restricted in their distribution compared to their D2 counterparts, several studies have shown that these receptors can couple to G-proteins that link to similar effector mechanisms that include the regulation of calcium currents and inhibition of adenylate cyclase (Seabrook et al, 1994a;Chio et al, 1994;McAllister et al, 1995 (DeMattos et al, 1993). Furthermore, in functional assays this ligand is an agonist at cloned human D3 receptors (McAllister et al, 1995) and also modulates midbrain dopamine cell function (DeWald et al, 1990). Estimates of the binding selectivity of agonists for D3 over D2 receptors are influenced by whether one compares the high or low affinity states of the receptors (e.g.…”
Section: Functional Effects Of (+)-Pd 128907mentioning
confidence: 99%
“…to the D2 receptor subtype (Chio et al, 1994;Seabrook et al, 1994a,b;Tang et al, 1994;McAllister et al, 1995). Consequently this study was carried out to determine whether D3 dopamine receptors are functional autoreceptors in rat brain.…”
Section: Introductionmentioning
confidence: 99%
“…A D 1 -like dopamine site, which couples to Gq/11 protein, has been linked to the modulation of phosphatidylinositol hydrolysis (Wang et al, 1995;Jin et al, 2001). On the other hand, D 2 -like dopamine receptors D 2 , D 3 , and D 4 are negatively coupled to adenylyl cyclase via Gi/o proteins (Onali et al, 1985;Potenza et al, 1994;Tang et al, 1994;McAllister et al, 1995). In addition, both D 1 and D 2 dopamine receptors have been shown to regulate calcium signaling (Missale et al, 1998) and to stimulate mitogen-activated protein kinase pathways (Zhen et al, 1998;Cai et al, 2000).…”
mentioning
confidence: 99%
“…However, measuring signaling events of the D 3 receptor appeared problematic (Freedman et al 1994;Tang et al 1994;McAllister et al 1995). Recently, we succeeded in the generation of transfected Chinese hamster ovary (CHO) cells permanently expressing high levels of either hD 2S , hD 2L , or hD 3 receptors.…”
Section: Introductionmentioning
confidence: 97%